2019
DOI: 10.1016/j.isci.2018.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Component Mechanism of H2 Relaxin Binding to RXFP1 through NanoBRET Kinetic Analysis

Abstract: SummaryThe peptide hormone H2 relaxin has demonstrated promise as a therapeutic, but mimetic development has been hindered by the poorly understood relaxin receptor RXFP1 activation mechanism. H2 relaxin is hypothesized to bind to two distinct ECD sites, which reorientates the N-terminal LDLa module to activate the transmembrane domain. Here we provide evidence for this model in live cells by measuring bioluminescence resonance energy transfer (BRET) between nanoluciferase-tagged RXFP1 constructs and fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 47 publications
2
39
0
Order By: Relevance
“…Additionally, the complex mechanism by which relaxin is now understood to bind RXFP1 (co‐ordinated by multiple distinct sites within the ECD) could also explain an apparently cooperative binding interaction when a receptor monomer is assumed. Furthermore, the most recent investigations into the kinetics of relaxin:RXFP1 binding found no evidence of negative binding cooperativity when relaxin dissociation rates were quantified in the presence of varying concentrations of competitor relaxin . Therefore, the most current evidence concerning the mode of relaxin binding to RXFP1 does not support the idea that it is activated as homodimer.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Additionally, the complex mechanism by which relaxin is now understood to bind RXFP1 (co‐ordinated by multiple distinct sites within the ECD) could also explain an apparently cooperative binding interaction when a receptor monomer is assumed. Furthermore, the most recent investigations into the kinetics of relaxin:RXFP1 binding found no evidence of negative binding cooperativity when relaxin dissociation rates were quantified in the presence of varying concentrations of competitor relaxin . Therefore, the most current evidence concerning the mode of relaxin binding to RXFP1 does not support the idea that it is activated as homodimer.…”
Section: Discussionmentioning
confidence: 93%
“…Tagging of GPCRs for BRET analysis often uses a variant of Renilla luciferase; however, this has been noted to adversely affect cell surface trafficking when tagged to the N‐terminus . To assess the possibility of BRET transfer between RXFP1 receptors suitably tagged at their N‐terminus, we used RXFP1 with Nanoluc at the N‐terminus and paired that with N‐terminally mCitrine tagged RXFP1 as the acceptor (Figure A). Importantly, both fusions (Nanoluc and mCitrine) were well tolerated and did not perturb relaxin‐mediated signaling from these receptors (Table and Figure B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since previous studies have shown how relaxin can alter the structural integrity of the ACL, the proposed relationship from the current study is not surprising. Although previous studies have established that there are relaxin receptors on the female ACL [26], the binding mechanism for relaxin on the ACL has not been established, but it is thought to be similar to relaxin binding to other parts of the body given the similarity in receptor [27]. Previous studies have also noted that estrogen amplified the effects of relaxin on the ACL [12].…”
Section: Discussionmentioning
confidence: 98%
“…Upon further investigation, relaxin was shown to exhibit a two-phase dissociation profile at the RXFP1 receptor, indicative of a multi-step binding process. In addition, the authors demonstrated that the receptor had at least two relaxin-bound states and that, when the linker region was removed, a single-step binding mechanism was achieved confirming that this region is important for ligand binding (Hoare et al, 2019). The ability to gain detailed time-resolved NanoBRET data on fluorescent ligand binding to the receptor was crucial for the interpretation of these data, and this would have been much more challenging to obtain with a traditional radioligand-binding assay.…”
Section: Ligand-binding Kineticsmentioning
confidence: 94%